KONFLIK DAN NEGOSIASI DI DALAM PERSPEKTIF: ARSITEKTUR, SOSIOLOGI, TEKNOLOGI DAN KOMUNIKASI - Santi Isnaini (Bricolage : Jurnal Magister Ilmu Komunikasi, 2018)
ABSTRACTThis article will provide a study of the concepts of conflict and negotiation in various scientific perspectives, which in this context will be seen from the perspective of architecture, sociology, technology and communication. Each perspective has its own perspective in defining and operationalizing a concept of conflict and negotiation, since each formal object of the scientific study has different ontological origins. For this reason through this article will be a basic topic development from various angles of scientific theories that will give a picture of the tradition of each of the scholars. For this reason, a comprehensive discussion of theoretical approaches to the basic topics of conflict and negotiation is required. So in this article the discussion will be divided into two big skeletons. The first will discuss the study of each discipline and its relation to communication. From several perspectives of architecture, sociology, and technology will be presented one by one epistemologis and study. Then from each perspective linked red thread with the tradition of communication science. The second major framework will address topics of conflict and negotiation from the various angles of the scholarship. After the previous discussion has been presented scientific approach, then will be dissected one by one how the scientific approach sees conflict and negotiation. Not only defining the concept of conflict and negotiation, the discussion will also link between each scientific perspective in conflict resolution through negotiation methods. Along with that will be described examples of cases that can clearly illustrate the use of conflict and negotiation topics in various scientific perspectives.Keywords: Conflict, Negotiation, Architecture, Sociology, Techonology, CommunicationABSTRAKArtikel ini akan memberikan sebuah telaah mengenai konsep konflik dan negosiasi di dalam berbagai perspektif keilmuan, yang dalam konteks ini akan dilihat melalui perspektif arsitektur, sosiologi, teknologi dan komunikasi. Setiap perspektif tersebut memiliki sudut pandangnya masing-masing dalam mendefisinikan maupun mengoperasionalkan sebuah konsep konflik dan negosiasi, mengingat setiap objek formal dari kajian keilmuan tersebut memiliki asal muasal ontologis yang berbeda. Untuk itulah melalui artikel ini akan dilakukan sebuah pengembangan topik dasar dari berbagai macam sudut pandang teori keilmuan yang akan memberikan gambaran tradisi dari masing-masing keilmuan. Untuk itulah diperlukan sebuah pembahasan yang komprehensif menyangkut berbagai pendekatan teoretis yang membahas topik dasar berupa konflik dan negosiasi. Sehingga dalam artikel ini pembahasan akan dibagi menjadi dua kerangka besar. Yang pertama akan membahas mengenai kajian dari masing-masing disiplin beserta kaitannya dengan komunikasi. Dari beberapa perspektif yaitu arsitektur, sosiologi, dan teknologi akan dipaparkan satu per satu epistemologis serta kajiannya. Kemudian dari tiap perspektif dihubungkan benang merahnya dengan tradisi keilmuan komunikasi. Kerangka besar kedua akan membahas topik konflik dan negosiasi dari berbagai sudut keilmuan tersebut. Setelah pada pembahasan sebelumnya telah dipaparkan pendekatan keilmuannya, selanjutnya akan dibedah satu per satu bagaimana pendekatan keilmuan tersebut memandang konflik dan negosiasi. Tidak hanya mendefinisikan konsep konflik dan negosiasi, pembahasan juga akan mengaitkan antara tiap perspektif keilmuan dalam penyelesaian konflik melalui metode negosiasi. Bersamaan dengan itu akan dijabarkan contoh kasus yang dapat menggambarkan secara jelas penggunaan topik konflik dan negosiasi dalam berbagai perspektif keilmuan.Kata kunci: Konflik, Negosiasi, Arsitektur, Sosiologi, Tekonologi, Komunikasi